Assessment of technical condition of forklift tires used in internal transport by studying damages and operating conditions - Gorzelańczyk, Piotr; Górniak, Wojciech (Ocena stanu technicznego opon wózków widłowych wykorzystywanych w transporcie wewnętrznym, 2019)
With the invention of the tyre, no one could have foreseen that over time it would perform such an important function, and without it industry, and everyday life would look completely different. Over time, the use of such an important innovation has created new challenges to be faced. Over the entire lifespan of the tyre, it gradually wears out or is suddenly damaged. An important issue is the ability to predict the remaining lifetime or eliminate any damage that may pose a threat in its further use. The aim of the article is to determine the technical condition of tires used in the selected company, by determining their age, damage, possibility of further use and those which should be withdrawn from service. The first part of the article presents the characteristics of forklift tyres, showing their construction, advantages and disadvantages, and the most common damage. Then the internal transport in which the forklift is used is characterized. In the next, main part of the article, the tyres of forklifts were examined, and the results and analysis of the measurements carried out were presented. The paper provides conclusion that arose during the performance of tests and solutions for users of the tested tyres
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2019, Nr 2 (33), s. 44-59